Loan supply and demand in Germany's three‐pillar banking system during the financial crisis. (15th January 2018) - Schmidt, Torsten; Zwick, Lina
Abstract: Internationally operating German banks had to depreciate huge amounts of assets during the financial crisis while the loan volume to the private sector declined simultaneously. In this paper, we empirically analyse, for the whole banking sector as well as for selected categories of banks, whether the reduction in loan volume was supply‐side‐driven. The results suggest that a credit crunch did not occur in Germany during the recent economic crisis. Apart from substantial policy interventions, our results offer two explanations: First, excess demand for loans dropped, as firms reverted to other external financing instruments, particularly industrial bonds. Second, those banks operating at the regional level only were not affected by the crisis. In this regard, the three‐pillar structure of the German banking system contributed to stable credit financing, as banks differ in their operating behaviours and in their customers.